Predicting the fire resistance of timber members loaded in tension - Fragiacomo, Massimo; Menis, Agnese; Moss, Peter J.; Clemente, Isaia; Buchanan, Andrew H.; De Nicolo, Barbara (Fire and materials, 2013)
SUMMARY The paper presents a numerical model for predicting the fire resistance of timber members. Fire resistance is evaluated in a two‐step process implemented in the Abaqus finite element code: first, a time‐dependent thermal analysis of the member exposed to fire and then a structural analysis under a constant load are performed. The structural analysis considers the reduction in mechanical properties (modulus of elasticity and strength) of timber with temperature. The analysis terminates when the member can no longer redistribute stresses from the hottest to the coldest parts, leading to structural failure. The model was used to simulate fire tests carried out on specimens made from laminated veneer lumber loaded in tension. Experimental data in terms of temperature, charring depth, displacement and failure time were compared with the numerical results obtained by assuming the thermal properties and degradation of mechanical properties with temperature as suggested by Eurocode 5, showing an overall acceptable approximation. The fire resistance of the timber member was then predicted depending upon the applied tensile loads using the numerical model and analytical formulas. The proposed finite element model can be used to predict the fire resistance of timber structures as an alternative to expensive and complicated experimental tests. Copyright © 2012 John Wiley & Sons, Ltd.